Endoscopic treatment of chronic pancreatitis: European Society of Gastrointestinal Endoscopy (ESGE) Guideline – Updated August 2018 - Dumonceau, Jean-Marc; Delhaye, Myriam; Tringali, Andrea; Arvanitakis, Marianna; Sanchez-Yague, Andres; Vaysse, Thierry; Aithal, Guruprasad P.; Anderloni, Andrea; Bruno, Marco; Cantú, Paolo; Devière, Jacques; Domínguez-Muñoz, Juan Enrique; Lekkerkerker, Selma; Poley, Jan-Werner; Ramchandani, Mohan; Reddy, Nageshwar; van Hooft, Jeanin E. (Endoscopy, 2019)
ESGE suggests endoscopic therapy and/or extracorporeal shockwave lithotripsy (ESWL) as the first-line therapy for painful uncomplicated chronic pancreatitis (CP) with an obstructed main pancreatic duct (MPD) in the head/body of the pancreas. The clinical response should be evaluated at 6 – 8 weeks; if it appears unsatisfactory, the patient’s case should be discussed again in a multidisciplinary team and surgical options should be considered.Weak recommendation, low quality evidence.ESGE suggests, for the selection of patients for initial or continued endoscopic therapy and/or ESWL, taking into consideration predictive factors associated with a good long-term outcome. These include, at initial work-up, absence of MPD stricture, a short disease duration, non-severe pain, absence or cessation of cigarette smoking and of alcohol intake, and, after initial treatment, complete removal of obstructive pancreatic stones and resolution of pancreatic duct stricture with stenting.Weak recommendation, low quality evidence.ESGE recommends ESWL for the clearance of radiopaque obstructive MPD stones larger than 5 mm located in the head/body of the pancreas and endoscopic retrograde cholangiopancreatography (ERCP) for MPD stones that are radiolucent or smaller than 5 mm. Strong recommendation, moderate quality evidence.ESGE suggests restricting the use of endoscopic therapy after ESWL to patients with no spontaneous clearance of pancreatic stones after adequate fragmentation by ESWL.Weak recommendation, moderate quality evidence.ESGE suggests treating painful dominant MPD strictures with a single 10-Fr plastic stent for one uninterrupted year if symptoms improve after initial successful MPD drainage. The stent should be exchanged if necessary, based on symptoms or signs of stent dysfunction at regular pancreas imaging at least every 6 months. ESGE suggests consideration of surgery or multiple side-by-side plastic stents for symptomatic MPD strictures persisting beyond 1 year after the initial single plastic stenting, following multidisciplinary discussion. Weak recommendation, low quality evidence.ESGE recommends endoscopic drainage over percutaneous or surgical treatment for uncomplicated chronic pancreatitis (CP)-related pseudocysts that are within endoscopic reach.Strong recommendation, moderate quality evidence.ESGE recommends retrieval of transmural plastic stents at least 6 weeks after pancreatic pseudocyst regression if MPD disruption has been excluded, and long-term indwelling of transmural double-pigtail plastic stents in patients with disconnected pancreatic duct syndrome.Strong recommendation, low quality evidence.ESGE suggests the temporary insertion of multiple side-by-side plastic stents or of a fully covered self-expandable metal stent (FCSEMS) for treating CP-related benign biliary strictures.Weak recommendation, moderate quality evidence.ESGE recommends maintaining a registry of patients with biliary stents and recalling them for stent removal or exchange.Strong recommendation, low quality evidence.